Estudio exploratorio para la determinación del coeficiente de balasto a partir de ensayos en laboratorio para suelos cohesivos - Cortés-Mena, Jonathan G. (Instituto Tecnológico de Costa Rica, 2010)
The resolution of the modulus of subgrade reaction is a really important and recognized topic speaking about structural foundations analysis. With this simple parameter it is possible to describe the behavior a specific soil will have when a certain foundation establishes on it. The common way for determining its value is by means of an essay what’s know as “Plate Load Test”, which, as well known when it’s done carefully, its offers really interesting results, actually, this essay is often complicated and even risky and this could easily show wrong results and the parameters would be inaccurate. For this reason, the previous research wants to establish the basis of an optional lab method for making a valuation that offers a reliable result of the value that the mentioned coefficient would show on the field. For making the essay the materials were analyzed from two different locations, on which ones, we had to make load test for getting a comparison according with the lab results. In the end, as a result of the load test made in the lab, we realized that the modulus of subgrade reaction obtained from this essay is approached to be twice the coefficient that the material would show on the field. Besides, this load test, that is proposed as an optional method for determining the modulus of subgrade reaction, at least for cohesive soils, also are exposed many comparisons of this coefficient with other essays like: CBR, Menard Pressuremeter, unconfined compression and added to this they were compared with empirical methods exposed by other authors.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2010.
Keywords: Balasto; Gravedad especifica; Humedad; Densidad; Presiómetro